Gejala Promiskuitas di Kalangan Anak pada Era Digital yang Menyebabkan Perkawinan Usia Anak - Agustino Crisna (Syntax Corporation Indonesia, 2023)
Dispensation of marriage is the granting of permission to marry by the court to a prospective husband/wife who is not yet 19 years old to enter into marriage. The authority of the court to grant marriage dispensation is regulated in Article 7 paragraph 2 of Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage. This study looks from a criminological point of view which is intended to be able to explore and analyze the rationality and effectiveness of social control that occurs as a result of early marriage. In addition, this study is expected to contribute to relevant stakeholders in terms of handling policies in preventing early marriage. The research method used in this study is a qualitative method with relevant resource persons in Ponorogo, as well as based on data obtained from the Religious Courts in Ponorogo. The results show that the promiscuity symptom affects the spike in early marriage cases in the Ponorogo area due to the role of digital technological advances that are not accompanied by supervision and regulations that need to be improved in several aspects of prevention.